Reconsidering the object of art : 1965-1975 - Goldstein, Ann; Jenkins, Susan L.; Koshalek, Richard; Lippard, Lucy R.; Melville, Stephen W.; Rorimer, Anne; Wall, Jeff (Cambridge : the MIT press, 1995)
Acconci, Vito ; Ader, Bas Jan ; Anselmo, Giovanni ; Antin, Eleanor ; Art & Language ; Asher, Michael ; Askevold, David ; Baldessari, John ; Barry, Robert ; Baumgarten, Lothar ; Becher, Bernd & Hilla ; Bochner, Mel ; Broodthaers, Marcel ; Brouwn, Stanley ; Buren, Daniel ; Burgin, Victor ; Cadere, Andre ; Coleman, James ; Darboven, Hanne ; Dibbets, Jan ; Downsbrough, Peter ; van Elk, Ger ; Fisher, Morgan ; Gilbert & George ; Graham, Dan ; Haacke, Hans ; Huebler, Douglas ; Jonas, Joan ; Kaltenbach, Stephen ; Kawara, On ; Knight, John ; Kosuth, Joseph ; Kozlov, Christine ; Lamelas, David ; Leavitt, William ; LeWitt, Sol ; Long, Richard ; Marioni, Tom ; Matta-Clark, Gordon ; N.E. Thing Co. ; Nauman, Bruce ; Nordman, Maria ; Oppenheim, Dennis ; Palermo, Blinky ; Paolini, Giulio ; Piper, Adrian ; Rainer, Yvonne ; Ruppersberg, Allen ; Ruscha, Edward ; Smithson, Robert ; Snow, Michael ; Toroni, Niele ; Wegman, William ; Weiner, Lawrence ; Wilson, Ian
Artists' selected bibliographies p. 310-320
Checklist of the exhibition p 321-335
Chronology of group exhibitions and reviews 1966-75 p. 276-291
General bibliography p. 293-309
Engels
Reconsidering the Object of Art : 1965-1975, The Museum of Contemporary Art, Los Angeles, 15 October 1995 - 4 February 1996.. Is part of the reopening of MOCA at the Temporary Contemporary.